2018
DOI: 10.1590/1980-5373-mr-2017-0933
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity Reduction of Nanostructured Undoped Zinc Oxide thin Films for Ag/ZnO Bilayers Using APCVD and Sputtering Techniques

Abstract: Nanostructured undoped zinc oxide (ZnO) thin films were deposited using atmospheric pressure chemical vapor deposition (APCVD) on glass substrates using zinc acetate dehydrate [C 4 H 6 O 4 Zn·2H 2 O, ZnAc] in less than 2 minutes for each sample. In order to reduce the resistivity of ZnO films, a very thin layer of Ag was deposited on top of the films via the sputtering method to reduce resistivity from 2.89 to 0.31 Ω.cm, using only a 30Å silver coating. Structural, electrical and optical properties of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 61 publications
(46 reference statements)
2
2
0
Order By: Relevance
“…On the other hand, the enhancement of resistivity in the range of 450 to 500 °C is due to the atomic composition of the semiconductor, that at 500 °C fits the perfect ZnO stoichiometry, as can be verified in figure 1. There are several reports [43][44][45] of temperature-dependent resistivity in ZnO thin films following the same resistivity evolution as ours. The comparison of the resistivity of the as-grown and irradiated ZnO thin films results is also exhibited in figure 8.…”
Section: Electrical Resultssupporting
confidence: 81%
“…On the other hand, the enhancement of resistivity in the range of 450 to 500 °C is due to the atomic composition of the semiconductor, that at 500 °C fits the perfect ZnO stoichiometry, as can be verified in figure 1. There are several reports [43][44][45] of temperature-dependent resistivity in ZnO thin films following the same resistivity evolution as ours. The comparison of the resistivity of the as-grown and irradiated ZnO thin films results is also exhibited in figure 8.…”
Section: Electrical Resultssupporting
confidence: 81%
“…Figure 5A and 5B depicted that the slop of sample annealed at 450℃ is greater than the sample annealed at 500℃ which indicated the change from ohmic behavior to Schottky-type behavior of junction with rising temperature. The electrical conductivity increases exponentially with increasing temperature (Figure 4A and 4B), hence follows the typical trend for semiconductor thin films [30] . Below 250K, the reverse bias current in both samples is higher than the forward bias current.…”
supporting
confidence: 70%
“…Resistivity increases as post-treatment temperature is increased. The phenomenon was reported by other authors [ 27 , 28 ], but the fullest explanation can be found in the work of Wisz [ 29 ]. Columnar growth of the ZnO layer with temperature is accompanied by increase of the layer resistance.…”
Section: Resultsmentioning
confidence: 64%